Online News Sites and Journalism 2.0: Reader Comments on Al Jazeera Arabic - Muhammad M. Abdul-Mageed (tripleC: Communication, Capitalism & Critique)
The current paper investigates reader commenting on news sites as one facet of journalism 2.0. Specifically, the themes, frequency, and regional coverage of readers’ comments—and in general, their activity levels and distribution—are considered, with a goal to increase knowledge of convergent media and computer-mediated communication (CMC), as well as shed light on the interactivity strategies adopted by influential news producers. The corpus is collected from the Arabic news site of the controversial Middle East-based, bilingual network Al Jazeera. Reader commenting was found to be a regular occurrence on the site but distributed unevenly across stories. The stories focused mostly on themes related to military and political violence, politics, and foreign relations, and covered events related to the Arab world more than other regions. Also, patterns of commenting varied according to day of the week and position of the story on the web page. Overall, these findings suggest that citizen journalism—journalism is performed by lay persons—on Al Jazeera tends to be shaped by the coverage and layout of the news site. Moreover, citizen participation in online news sites such as Al Jazeera is still far from ideal, in that commenters are given neither the access nor the facilitation to use modalities other than written text. These limitations are critiqued in light of contemporary discourses about media convergence and journalism 2.0.